The Lateral suppressor (Ls) gene of tomato encodes a new member of the VHIID protein family - Schumacher, Karin; Schmitt, Thomas; Roßberg, Mathias; Schmitz, Gregor; Theres, Klaus (Proceedings of the National Academy of Sciences of the United States of America, 1999)
The ability of the shoot apical meristem to multiply and distribute its meristematic potential through the formation of axillary meristems is essential for the diversity of forms and growth habits of higher plants. In the lateral suppressor mutant of tomato the initiation of axillary meristems is prevented, thus offering the unique opportunity to study the molecular mechanisms underlying this important function of the shoot apical meristem. We report here the isolation of the Lateral suppressor gene by positional cloning and show that the mutant phenotype is caused by a complete loss of function of a new member of the VHIID family of plant regulatory proteins.